Breeding systems in Balsaminaceae in relation to pollen/ovule ratio, pollination syndromes, life history and climate zone. (24th September 2018) - Lozada‐Gobilard, S.; Weigend, M.; Fischer, E.; Janssens, S. B.; Ackermann, M.; Abrahamczyk, S.
Abstract: Pollen/ovule (P/O) ratios are often used as proxy for breeding systems. Here, we investigate the relations between breeding systems and P/O ratios, pollination syndromes, life history and climate zone in Balsaminaceae. We conducted controlled breeding system experiments (autonomous and active self‐pollination and outcrossing tests) for 65 Balsaminaceae species, analysed pollen grain and ovule numbers and evaluated the results in combination with data on pollination syndrome, life history and climate zone on a phylogenetic basis. Based on fruit set, we assigned three breeding systems: autogamy, self‐compatibility and self‐incompatibility. Self‐pollination led to lower fruit set than outcrossing. We neither found significant P/O differences between breeding systems nor between pollination syndromes. However, the numbers of pollen grains and ovules per flower were significantly lower in autogamous species, but pollen grain and ovule numbers did not differ between most pollination syndromes. Finally, we found no relation between breeding system and climate zone, but a relation between climate zone and life history. In Balsaminaceae reproductive traits can change under resource or pollinator limitation, leading to the evolution of autogamy, but are evolutionary rather constant and not under strong selection pressure by pollinator guild and geographic range changes. Colonisation of temperate regions, however, is correlated with transitions towards annual life history. Pollen/ovule‐ratios, commonly accepted as good indicators of breeding system, have a low predictive value in Balsaminaceae. In the absence of experimental data on breeding system, additional floral traits (overall pollen grain and ovule number, traits of floral morphology) may be used as proxies.